The The Application of Public Speaking Training in Enhancing the Quality of Human Resources at PT. Asri Dharma Sejahtera - Bimo Kuncoro Dion Bimantaka; Rio Candra Pratama (ARRUS Journal of Social Sciences and Humanities, 2025)
This Industrial Internship Report examines the implementation of public speaking training to enhance human resource quality at PT. Asri Dharma Sejahtera, Bojonegoro. The internship was conducted for one month in the Human Resource Development (HRD) division, focusing on improving employees' communication skills and workplace performance. The primary objective of the training was to strengthen public speaking competence, boost self-confidence, and support organizational productivity. Data collection methods included direct observation, interviews with HRD personnel, and document analysis of the training process. The findings indicate that the program significantly improved employees' presentation abilities, body language utilization, and systematic message delivery. Challenges encountered included differences in participants’ backgrounds, limited training materials, varying levels of trainer expertise, and inadequate supporting facilities. Proposed solutions involve refining training content, improving trainer qualifications, and optimizing training facilities to ensure effective learning outcomes. This internship provided practical experience in HRD operations and emphasized the strategic role of communication skills in driving organizational performance. The results are expected to serve as a reference for future training initiatives aimed at sustainable human resource development.